2012
DOI: 10.1155/2012/540597
|View full text |Cite
|
Sign up to set email alerts
|

Serum Homocysteine, Vitamin B12, Folic Acid Levels and Methylenetetrahydrofolate Reductase (MTHFR) Gene Polymorphism in Vitiligo

Abstract: Abstract. The aim of this study was to determine serum vitamin B12, folic acid and homocysteine (Hcy) levels as well as MTHFR (C677, A1298C) gene polymorphisms in patients with vitiligo, and to compare the results with healthy controls. Forty patients with vitiligo and 40 age and sex matched healthy subjects were studied. Serum vitamin B12 and folate levels were determined by enzyme-linked immunosorbent assay. Plasma Hcy levels and MTHFR polymorphisms were determined by chemiluminescence and real time PCR meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 12 publications
3
27
0
Order By: Relevance
“…The effects of rs1801131 on MTHFR activity or Hcy level in human diseases remain controversial. In our study, we did not find any statistical relationship between rs1801131 and vitiligo risk, which is consistent with the study of vitiligo in the Turkish population …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The effects of rs1801131 on MTHFR activity or Hcy level in human diseases remain controversial. In our study, we did not find any statistical relationship between rs1801131 and vitiligo risk, which is consistent with the study of vitiligo in the Turkish population …”
Section: Discussionsupporting
confidence: 92%
“…However, the underlying mechanism remains unclear and needs to be explored further in molecular research. The association of MTHFR polymorphisms with vitiligo risk has been studied in the Turkish population . However, no evidence was found that MTHFR mutations (rs1801133 and rs1801131) were related to either vitiligo susceptibility or Hcy level in the Turkish population study, negative results from which may mostly be due to a relative smaller sample size of 40 cases and 40 controls.…”
Section: Discussionmentioning
confidence: 99%
“…published a comprehensive review of 33 claimed vitiligo candidate genes ( ACE , AIRE , CAT , CD4 , CLEC11A , COMT , CTLA4 , C12orf10 , DDR1 , EDN1 , ESR1 , FAS , FBXO11 , FOXD3 , FOXP3 , GSTM1 , GSTT1 , IL1RN , IL10 , KITLG , MBL2 , NFE2L2 , PDGFRA‐KIT , PTGS2 , STAT4 , TAP1‐PSMB8 , TGFBR2 , TNF , TSLP , TXNDC5 , UVRAG , VDR , XBP1 ), finding support for only three ( TSLP , XBP1 , FOXP3 ) in analysis of a genome‐wide vitiligo GWAS dataset . Additional claimed candidate gene associations with vitiligo include AHR , COX2 , GSTP1 , IL4 , IL19 and IL20RB , INOS , PRO2268 , TLR2 and TLR4 , while candidate genes reported not to be associated include CD28 , ICOS , IL20 , IL24e and IL20RA , MTHFR , and SMOC2 . Some of these claimed novel candidate gene associations may be valid, though most are likely to represent false‐positives.…”
Section: Molecular Genetic Eramentioning
confidence: 99%
“…Most vitiligo susceptibility loci encode melanocyte components, and antioxidant and immune-regulatory proteins [40,246]. For example, associations have been established between vitiligo pathogenesis and polymorphisms in tyrosinase (TYR) [247], catalase (CAT) [65], glutathione peroxidase (GPX) [65], melanocortin 1 receptor (MC1R) [248], major histocompatibility complex (MHC) [249], NACHT leucine-rich repeat protein 1 (NLRP1) [172] [252]. Both protective and susceptibility-increasing effects have been found in the case of different polymorphisms in these genes [253,254].…”
Section: Cross Talk Between Oxidative Stress Er Stress and Immune Symentioning
confidence: 99%